Peran Lingkungan Kerja dan Kompensasi dalam Meningkatkan Motivasi Kerja Dosen - Harras, Hadyati (Sekolah Menengah Kejuruan (SMK) Pustek, 2025)
This study examines the factors influencing lecturers' work motivation at the Management Bachelor's Program, Universitas Pamulang, focusing on the role of work environment and compensation. The background of this research is rooted in the need to understand how these factors can impact lecturers' motivation to improve teaching and academic performance. The objective is to determine the significant influence of work environment and compensation on lecturers' work motivation. A quantitative research method was employed using a survey approach with a simple random sampling technique. Data were collected through questionnaires distributed via Google Forms to 140 lecturers. Data analysis was conducted using multiple linear regression and descriptive statistics, with validity and reliability tests applied. The findings reveal that both work environment and compensation have a significant positive impact on work motivation, with work environment contributing 32.9% and compensation contributing 25.7%. The coefficient of determination indicates that 67.5% of the variation in work motivation can be explained by these two factors. The implications of this research suggest that universities should prioritize improving work environment quality and compensation systems to enhance lecturers' motivation. This can lead to better academic performance and higher job satisfaction. Future research could explore additional factors influencing work motivation.